PENGARUH BUDAYA ORGANISASI TERHADAP NILAI PERUSAHAAN DAN GCG SEBAGAI VARIABEL MODERATING - Verliani Dasmaran (Program Studi Akuntansi, 2018)
Abstract The purpose of this study is To know how the influence of organizational culture on Corporate Value and To Know how Good Corporate Governance can strengthen the influence of organizational culture on corporate value, the study population is 30 companies registered in CGPI (Coorporate Governance Persepsion Index) in 2015 and the sample research into 25 companies with research methods The type of research used is associative research that is associative technique of associative research using quantitative analysis technique (statistic). To know the amount of influence between variable of writer use data analysis with help SPSS 22 : The result of research proves that there is positive influence of Organization Culture to Company Value or hypothesis (H1) accepted, and H2 rejected means Good Corporate Governance (GCG) Minimize the Effect of Organizational Culture Variables on Corporate Value. . Keyword : organizational culture, Good Corporate Governance, Corporate Value